Simultaneous Estimation of Amlodipine Besylate and Nebivolol Hydrochloride in Pharmaceutical Tablets Formulation by RP-HPLC Using PDA Detector: Simultaneous estimation of amlodipine besylate and nebivolol hydrochloride - Ashutosh Kumar; Manidipa Debnath; Mendeli Sreenu; Mahesh Kumar Singh (Iranian Journal of Pharmaceutical Sciences, 2018)
The present work was undertaken with the aim to develop and validate a rapid and consistent RP-HPLC method in which the peaks will be appear with short period of time as per ICH Guidelines.The separation was achieved on a stainless steel analytical column, Eclipse XDB plus C18 column (4.6 X 150 mm; 5 μm) in an isocratic mode. The mobile phase was composed acetonitrile and 0.01 M ammonium acetate (pH adjusted to 4.5 using glacial acetic acid), which were mixed in the ratio of 50: 50. The flow rate was monitored at 1.0 mL/min. The wavelength selected for detection was 265 nm. The retention time found for amlodipine besylate and nebivolol hydrochloride was 2.967 and 3.510 min, respectively. The % recovery was 100.20- 100.86 for amlodipine and 100.20 - 100.78 for nebivolol. The linearity was established in the range of 5-25 μg/mL for amlodipine and 10-50 μg/mL for nebivolol. The slope, intercept, and correlation coefficient were found to be 314.2x, +162.4, and 0.999 for amlodipine besylate and 248x, -305.7, and 0.9998 for nebivolol hydrochloride, respectively. The limits of detection for amlodipine besylate and nebivolol hydrochloride obtained by the proposed method was 0.07 and 0.20 μg/ml and the limits of quantification for amlodipine besylate and nebivolol hydrochloride obtained by the proposed method was 0.23 and 0.61 μg/mL, respectively. The method was found to be suitable for the quality control test of amlodipine besylate and nebivolol hydrochloride simultaneously in a bulk drugs as well as in a formulations.